Perbandingan Slow Deep Breathing dengan Kombinasi Back Massage dan Slow Deep Breathing terhadap Tekanan Darah Pasien Hipertensi - Ramadhan Trybahari; Busjra Busjra; Rohman Azzam (Journal of Telenursing (JOTING), 2019)
This study aims to determine the effect of combination therapy back massage and slow deep breathing on changes in blood pressure in hypertensive patients. Quantitative study non equivalent control group pretest - posttest design. The results showed that there was a significant difference in blood pressure between the combined intervention group BM and SDB and SDB group (p = 0.000; α = 0.05) on systolic and diastolic blood pressure on the fifth day. In conclusion, the combination technique of BM and SDB is an effective attempt to change blood pressure. Keywords: Back Massage, Hypertension, Slow Deep Breathing